Polygonatum cyrtonema var. gutianshanicum——A new variety of Polygonatum cyrtonema and comparative studies on it and the similar species - JIN Xiao feng; QIU Ying-xiong; DING Bing-yang (浙江大学学报. 农业与生命科学版)
In this paper, a new variety of Polygonatum cyrtonema——P. cyrtonema var. guitanshancum was discribed. Karyotypical and morphological studies of it and the similar specics were also giv en. The karyotype of the variety is formulated as 2n=24=14 m+4 sm+6 st (2 sc). P. cyrtonema is 2n=22=10 m+8sm+4 st, and P. filipes is 2n=16=8m (4 sat)+8sm. The karyotype of P. filipes is bimodal and belongs to Stebbins' 2B type, while P. cyrtonema to 3B type and the variety to 2C type. The karyotypes were firstly reported. Based upon morphological analysis, the leaf width and peduncle length were considered to be the main difference between P. cyrtonema var. gutianshanicum and P. cyrtonema var. cyrtonema.